![\boxed {\boxed{ { \red{ \bold{ \underline{Question:-}}}}}} \boxed {\boxed{ { \red{ \bold{ \underline{Question:-}}}}}}](https://tex.z-dn.net/?f=%5Cboxed+%7B%5Cboxed%7B+%7B+%5Cred%7B+%5Cbold%7B+%5Cunderline%7BQuestion%3A-%7D%7D%7D%7D%7D%7D)
Solve the following pair of linear equations by the substitution method :-
![\frac{3x}{2} - \frac{5y}{3} = - 2 \\ \frac{x}{3} + \frac{y}{2} = \frac{13}{6} \frac{3x}{2} - \frac{5y}{3} = - 2 \\ \frac{x}{3} + \frac{y}{2} = \frac{13}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B3x%7D%7B2%7D++-++%5Cfrac%7B5y%7D%7B3%7D++%3D++-+2+%5C%5C++%5Cfrac%7Bx%7D%7B3%7D++%2B++%5Cfrac%7By%7D%7B2%7D++%3D++%5Cfrac%7B13%7D%7B6%7D+)
![\bold\dag \bold{ \: No \: spams \:or \: Copied \: answers \: !} \bold\dag \bold{ \: No \: spams \:or \: Copied \: answers \: !}](https://tex.z-dn.net/?f=+%5Cbold%5Cdag+%5Cbold%7B+%5C%3A+No+%5C%3A+spams+%5C%3Aor+%5C%3A+Copied+%5C%3A+answers+%5C%3A+%21%7D)
Answers
EXPLANATION.
Pair of linear equations.
⇒ 3x/2 - 5y/3 = - 2. - - - - - (1).
⇒ x/3 + y/2 = 13/6. - - - - - (2).
As we know that,
From equation (1) & (2), we get.
⇒ 9x - 10y = - 12. - - - - - (1).
⇒ 2x + 3y = 13. - - - - - (2).
Multiply equation (1) by 3, we get.
Multiply equation (2) by 10, we get.
⇒ 9x - 10y = - 12. - - - - - (1). x 3.
⇒ 2x + 3y = 13. - - - - - (2). x 10.
We get,
⇒ 27x - 30y = - 36. - - - - - (3).
⇒ 20x + 30y = 130. - - - - - (4).
Adding equation (3) & (4), we get.
⇒ 47x = 94.
⇒ x = 2.
Put the value of x = 2 in equation (1), we get.
⇒ 9x - 10y = - 12. - - - - - (1).
⇒ 9(2) - 10y = - 12.
⇒ 18 - 10y = - 12.
⇒ - 10y = - 12 - 18.
⇒ - 10y = - 30.
⇒ 10y = 30.
⇒ y = 3.
Values of x = 2 & y = 3.
Given :-
3x/2 - 5y/3 = -2
9x - 10y/6 = -2
9x - 10y = -2 × 6
9x - 10y = -12 (1)
x/3 + y/2 = 13/6
2x + 3y/6 = 13/6
2x + 3y = 13 (2)
Multiply the equation 1 by 3
3(9x - 10y) = 3(-12)
27x - 30y = -36
Multiply the equation 2 by 10
10(2x + 3y) = 10(13)
20x + 30y = 130
Add both
27x - 30y + 20x + 30y = -36 + 130
27x + 20x = -94
47x = -94
x = -94/47
x = -2
Using 2
2x + 3y = 13
2(-2) + 3y = 13
-4 + 3y = 13
3y = 13 - 4
3y = 9
y = 9/3
y = 3
[tex][/tex]